Lean thinking: from the shop floor to an organizational culture - Amaro, Paulo (2020)
In many areas, there is a multitude of terms/designations and definitions for the same concept, leading thus to misunderstanding. This also occurs with the designated Lean Production, which started to be known as a “thing” from the shop floor. However, it was quickly realized that it is much more than that (and should be understood as much more), otherwise the transformation of the operations will not be possible, as each company has its own organizational culture that could enable or inhibit the Lean implementation. Lean Production is underneath Lean Thinking, otherwise designated as philosophy, organizational culture, organizational model, production paradigm and others. This paper intends to present terms/designations and definitions that had been associated with Lean Thinking. The objective is to clarify that Lean Thinking is, in fact, all of that. Companies need to understand this in order to improve their operations, by recognizing value for the customer and eliminate wastes.